1987
DOI: 10.1104/pp.84.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inhibition of Lignification in Bryonia dioica

Abstract: Rubbing-induced lignification in Bryonia dioica internodes is significantly impaired by N(o-hydroxyphenyl) and N(o-aminophenyl) sulfinamoyl tertiobutyl acetate, specific inhibitors of cinamyl alcohol dehydrogenase, an enzyme which is strictly associated with lignin monomer synthesis. Along with the reduction of lignification, these inhibitors counteract the inhibition of elogtion due to rubbing. These results indicate that lignification participates in the thigmomorphogenetic growth response of Bryonia dioica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Plants typically acclimate to such disturbances via developmental responses that modulate the mechanical properties of load-bearing tissues and organs. Reduction of mechanical loads on the stem is achieved, for example, by a reduction in elongation, while stem thickening, increased production of support tissues, and cell-wall lignification promote stem flexural rigidity (Biddington, 1986;Dejaegher and Boyer, 1987;Niklas 1998;Patterson, 1992;Braam, 2005;Chehab et al, 2009;Porter et al, 2009;Saidi et al, 2009;Coutand, 2010). Alternative strategies involve reducing the risk of stress-induced breakage by enhancing tissue flexibility, as observed in mechanically perturbed leaf petioles and the stems of some species (Biddington, 1986;Liu et al, 2007;Anten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Plants typically acclimate to such disturbances via developmental responses that modulate the mechanical properties of load-bearing tissues and organs. Reduction of mechanical loads on the stem is achieved, for example, by a reduction in elongation, while stem thickening, increased production of support tissues, and cell-wall lignification promote stem flexural rigidity (Biddington, 1986;Dejaegher and Boyer, 1987;Niklas 1998;Patterson, 1992;Braam, 2005;Chehab et al, 2009;Porter et al, 2009;Saidi et al, 2009;Coutand, 2010). Alternative strategies involve reducing the risk of stress-induced breakage by enhancing tissue flexibility, as observed in mechanically perturbed leaf petioles and the stems of some species (Biddington, 1986;Liu et al, 2007;Anten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…de Jaegher et al (1985) found that rubbing the internodes of Bryonia dioica results in increased lignin, decreased cellulose and increased activities of phenylalanine ammonia-lyase and cell wall peroxidases. Furthermore, the chemical inhibition of lignin synthesis significantly counteracts the reduction of internode elongation, suggesting a direct role of lignification in thigmomorphogenetic growth responses (de Jaegher and Boyer, 1987). Alteration of chlorophyll content has also been associated with mechanical perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have been published concerning the mechanism that could explain the modification of B. dioica internode growth induced by a mechanical stimulus (Boyer et al, 1979(Boyer et al, , 1983(Boyer et al, , 1986De Jaegher et al, 1985;De Jaegher and Boyer, 1987;Bourgeade et al, 1991;Galaud et al, 1993;Thonat et al, 1993;Bourgeade and Boyer, 1994;Mathieu et al, 1995). Among the processes that seem to be rapidly affected by this stimulus are the modifications of plasma membrane lipids (Mathieu et al, 1995), Ca 2+ redistribution (Thonat et al, 1993), and the expression of a calmodulin gene (Galaud et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This process is known as thigmomorphogenesis, a developmental response in plants to a mechanical stress (Jaffé, 1973). Previous' studies have shown that this process involves a rapid increase of peroxidase activity, an acceleration of lignification (De Jaegher et al, 1985;De Jaegher and Boyer, 1987), and a transient increase of ethylene .production (Boyer et al, 1983(Boyer et al, , 1986. The external stimulation affects the plasma membrane H+-ATPase activity and induces an increase of plasma membrane fluidity with modifications of some membrane components (Bourgeade and Boyer, 1994;Mathieu et al, 1995).…”
mentioning
confidence: 99%